Tailoring the Interfacial Band Offset by the Molecular Dipole Orientation for a Molecular Heterojunction Selector. Issue 21 (9th September 2021) - Eo, Jung Sun; Shin, Jaeho; Yang, Seunghoon; Jeon, Takgyeong; Lee, Jaeho; Choi, Sanghyeon; Lee, Chul‐Ho; Wang, Gunuk
Abstract: Understanding and designing interfacial band alignment in a molecular heterojunction provides a foundation for realizing its desirable electronic functionality. In this study, a tailored molecular heterojunction selector is implemented by controlling its interfacial band offset between the molecular self‐assembled monolayer with opposite dipole orientations and the 2D semiconductor (1L ‐MoS2 or 1L ‐WSe2 ). The molecular dipole moment direction determines the direction of the band bending of the 2D semiconductors, affecting the dominant transport pathways upon voltage application. Notably, in the molecular heterostructure with 1L ‐WSe2, the opposite rectification direction is observed depending on the molecular dipole moment direction, which does not hold for the case with 1L ‐MoS2 . In addition, the nonlinearity of the molecular heterojunction selector can be significantly affected by the molecular dipole moment direction, type of 2D semiconductor, and metal work function. According to the choice of these heterojunction constituents, the nonlinearity is widely tuned from 1.0 × 10 1 to 3.6 × 10 4 for the read voltage scheme and from 0.4 × 10 1 to 2.0 × 10 5 for the half‐read voltage scheme, which can be scaled up to an ≈482 Gbit crossbar array. Abstract : By tailoring the interfacial band offset with the molecular dipole orientation, molecular heterojunction selector is presented. Based on diverse interfacial band offsets achieved by changing the heterojunction constituents, such as the molecular dipole moment direction, types of two‐dimensional transition metal dichalcogenide, and work function of the electrodes, the nonlinearity is widely tuned, scaling up to an ≈482 Gbit crossbar array.